Real wage cyclicality in Italy - Fei Peng; William Stanley Siebert (Institute for the Study of Labor (IZA), 2006)
This paper analyzes the cyclical behaviour of male real wages in Italy using the European Community Household Panel 1994-2001. We distinguish between job stayers (remaining in the same job), and within- and between-company job movers. Stayers are the large majority. We find stayers in Northern Italy to have high cyclicality of real wages, higher in fact than the US and the UK. The Northern cyclicality is significant for all sub-samples (except for public sector workers), and higher in small firms, the private sector, and for temporary workers, as expected. In contrast, we find little wage cyclicality for any sub-group in the Centre-South, even for workers in small private sector firms. Evidently, labour markets in the North of Italy operate much more competitively than in the Centre and South.
urn:nbn:de:101:1-2008060639
Keywords: 330